"Not just the consequences, but also the pleasurable sex": a review of the content of comprehensive sexuality education for early adolescents in Rwanda - Valens Mbarushimana; Susan Goldstein; Daphney Nozizwe Conco (BMC, 2023)
Abstract Background Responding to adolescents' educational needs in sexual and reproductive health and rights (SRHR) is central to their sexual health and achieved through school-based comprehensive sexuality education (CSE). In 2016, Rwanda introduced CSE through the competence-based curriculum in schools to enhance learners' knowledge about sexuality, gender, and reproductive health issues, including HIV/AIDS. However, globally, the content of CSE is sometimes dissimilar, and little evidence surrounds its scope in many settings, including Rwanda. In addition, the extent to which CSE aligns with international guidelines has yet to be well known. This study assesses major areas of CSE for early adolescents in Rwanda, analyses how CSE correlates with international guidelines and makes recommendations accordingly. Methods We reviewed the Rwandan competence-based curriculum to map CSE competences for early adolescents and conducted semi-structured interviews with key informants (N = 16). Eleven of the 23 curriculum documents met the selection criteria and were included in the final review. We manually extracted data using a standard form in Microsoft Excel and analysed data using frequency tables and charts. Interviews were thematically analysed in NVivo 11 for Windows. Findings We found 58 CSE competences for early adolescents across various subjects, increasing with school grades. All recommended CSE areas were addressed but to a variable extent. Most competences fall under four recommended areas: sexual and reproductive health; human body and development; values, rights, and sexuality; and understanding gender. The least represented area is violence and staying safe. Of the 27 expected topics, there are two to six CSE competences for 13 topics, one CSE competence for each of the six others, and none for the eight remaining ones. Qualitative findings support these findings and suggest additional content on locally controversial but recommended areas of sexual pleasure, orientation, desire and modern contraceptive methods. Conclusion This study explores the CSE content for early adolescents in Rwanda and how they align with sexuality education standards. Ensuring equal coverage of CSE areas and addressing missing topics may improve CSE content for this age group and foster their SRHR.